2023
DOI: 10.3389/fpls.2023.1043354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of source-sink regulation and nodal position of the main crop on the sprouting of regenerated buds and grain yield of ratoon rice

Abstract: Ratoon rice (Oryza sativa L.) is the production of a second season rice that utilizes the dormant buds surviving on the stubble left behind after the harvest of the main crop. However, the sprouting mechanism of regenerated buds at separate nodes is rarely reported. Field experiments were conducted to examine the effects of leaf-cutting and spikelet thinning on the sprouting of regenerated buds at the separate node, the contributions of regenerated panicles at the separate node to the total grain yield in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…In a related study, the ABA content in rice crops increased steadily, triggering a sharp increase in the crop panicle weight 20 days after heading [42]. Our investigation showed that ABA exhibited a linear increase in both PR25 and AR2640, exhibiting the highest peak 22 d after harvest, especially at low stubble heights, corroborating He et al's work [43], wherein they documented that ABA was responsible for ratoon rice panicle regeneration. This behavior confirms Fallah et al's recent findings, wherein they mentioned that ABA enrichment contributed to the promotion of sugarcane ratoon crop growth [41].…”
Section: Discussionsupporting
confidence: 89%
“…In a related study, the ABA content in rice crops increased steadily, triggering a sharp increase in the crop panicle weight 20 days after heading [42]. Our investigation showed that ABA exhibited a linear increase in both PR25 and AR2640, exhibiting the highest peak 22 d after harvest, especially at low stubble heights, corroborating He et al's work [43], wherein they documented that ABA was responsible for ratoon rice panicle regeneration. This behavior confirms Fallah et al's recent findings, wherein they mentioned that ABA enrichment contributed to the promotion of sugarcane ratoon crop growth [41].…”
Section: Discussionsupporting
confidence: 89%
“…The buds remain incapable of initiating sprouting and generating fresh branches or foliage. However, if the adjacent tissue is removed, the dormant buds can resume growth quickly [16,17]. Significant progress has been made in studying the complexities of paradormancy, especially in understanding the mechanisms behind apical dominance [18][19][20].…”
Section: Key Development Stages and Regulations Of Bud Annual Growth ...mentioning
confidence: 99%
“…Because ratoon rice has the advantages of saving costs, increasing income, increasing yield and reducing labor intensity, people have begun to focus on ratoon rice again. Owing to the selection of high-yield and high-quality varieties of ratoon rice, the optimization of nutrient and water management, research and development of comprehensive pest and disease prevention and control technology, and the matching of agricultural machinery and agronomy, the yield of ratoon rice has been greatly improved ( Huang et al., 2022 ; He et al., 2023 ). The long grain filling time during the ratoon crop of ratoon rice allows sufficient accumulation of photosynthetic products, which is conducive to the formation of good rice quality ( Li et al., 1990 ).…”
Section: Introductionmentioning
confidence: 99%